Lexical features of emphasis in the Swiss national variant of French language - E G Dmitrieva (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2011)
The article is dedicated to the emphasizing words and expressions used in the Swiss national variant of the French language; the issues of the language social role as well as the problems of intercultural communication are also touched upon.